The 95RGD97 sequence on the Aα chain of fibrinogen is essential for binding to its erythrocyte receptor - Carvalho FA (Dove Medical Press, 2018)
Filomena A Carvalho,1,* Ana Filipa Guedes,1,* Cedric Duval,2 Fraser L Macrae,2 Luke Swithenbank,2 David H Farrell,3 Robert AS Ariëns,2 Nuno C Santos1 1Instituto de Medicina Molecular, Faculdade de Medicina, Universidade de Lisboa, Lisbon, Portugal; 2Theme Thrombosis, Division of Cardiovascular and Diabetes Research, Leeds Institute for Genetics, Health and Therapeutics, University of Leeds, Leeds, UK; 3Department of Surgery, Oregon Health and Science University, Portland, OR, USA *These authors contributed equally to this work Background: Erythrocyte aggregation, a cardiovascular risk factor, is increased by high plasma fibrinogen levels. Here, the effect of different fibrinogen mutations on binding to its human erythrocyte receptor was assessed in order to identify the interaction sites. Methods: Three fibrinogen variants were tested, specifically mutated in their putative integrin recognition sites on the Aα chain (mutants D97E, D574E and D97E/D574E) and compared with wild-type fibrinogen. Results: Atomic force microscopy-based force spectroscopy measurements showed a significant decrease both on the fibrinogen–erythrocyte binding force and on its frequency for fibrinogen with the D97E mutation, indicating that the corresponding arginine–glycine–aspartate sequence (residues 95–97) is involved in this interaction, and supporting that the fibrinogen receptor on erythrocytes has a β3 subunit. Changes in the fibrin clot network structure obtained with the D97E mutant were observed by scanning electron microscopy. Conclusion: These findings may lead to innovative perspectives on the development of new therapeutic approaches to overcome the risks of fibrinogen-driven erythrocyte hyperaggregation. Keywords: atomic force microscopy, fibrinogen, fibrin clot, erythrocyte aggregation, mutant protein